The Importance of Educating Couples about the Role of Teleworking in Couple Satisfaction - Andreea Girnet (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The aim of this research is to investigate the implications that personality, from a Big5 perspective, can have on the satisfaction felt in the couple, as well as job satisfaction in the context of teleworking. The present study presents a correlational and comparative design, non-experimental. Participants (N = 126) were collected online, representing people who were in a relationship and who had to work from home, on whom a personality measurement inventory and two satisfaction level measuring instruments were applied. The results recorded that aspects of personality such as extraversion, agreeableness and openness to experience have managed to significantly predict job satisfaction.